Phylogenetics of the mycoheterotrophic genus Thismia (Thismiaceae: Dioscoreales) with a focus on the Old World taxa: delineation of novel natural groups and insights into the evolution of morphological traits. (4th April 2020) - Shepeleva, Ekaterina A; Schelkunov, Mikhail I; Hroneš, Michal; Sochor, Michal; Dančák, Martin; Merckx, Vincent Sft; Kikuchi, Izai Abs; Chantanaorrapint, Sahut; Suetsugu, Kenji; Tsukaya, Hirokazu; Mar, Shek S; Luu, Hong Truong; et al.
Abstract: Thismia is a genus of > 80 mycoheterotrophic species characterized by a peculiar appearance and complex floral morphology. A significant proportion of the species and morphological diversity of Thismia has only been uncovered in the past two decades, and new discoveries continue to be made. Given that many new data have recently become available, and the most comprehensive taxonomic revision of the genus from 1938 addresses less than half of the currently known species, previous hypotheses for species relationships and infrageneric taxonomic classification in Thismia was in need of review. Extensive molecular phylogenetic studies of Thismia at the genus level have never been presented. We investigate the phylogenetic relationships of 41 species (and one variety) of Thismia from the Old World. Our study comprises 68 specimens (for 28 of which the data were newly generated), including outgroup taxa broadly representing Thismiaceae (= Burmanniaceae p.p . sensu APG IV, 2016 ), and is based on two nuclear and one mitochondrial marker. We use maximum likelihood and Bayesian inference to infer relationships among the taxa. We also constructed a morphological dataset of 12 mostly floral characters, comparing these characters to hypotheses based on molecular evidence to identify putative synapomorphies for major clades and to discuss hypotheses regarding the evolution of structural traits in the genus. Our analyses indicate that the majority of currently accepted infrageneric taxa of Thismia are polyphyletic. We find support for the monophyly of the Old World group, in which we recognize five well-supported lineages (clades); the only New World species studied appears to be related to the Neotropical genus Tiputinia . Ancestral state reconstructions demonstrate that the evolution of most morphological characters was homoplastic, but we identify characters that provide each of the five clades of Old World Thismia with a unique morphological description. The geographical distribution of the species under study is also shown to be consistent with the major clades. Our investigation provides a phylogenetic basis for the development of a novel sectional classification of Thismia reflecting morphological and geographical traits.